Dinamika Belanja Online: Analisis Kondisi Ekonomi Pengguna TikTok Shop - Wini Anisa Apriliani; Riva Zahra Rizkyani; Nabila Khairunnisa; Dafha Priatama; Khansa Aulia Syahidah; Bagas Putra Budiono; Rama Wijaya Abdul Rozak (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Economic condition is an essential thing that needs to be considered as a reflection of fulfilling needs with a lifestyle that is in accordance with the separation between needs and desires. The purpose of this study was to determine the economic conditions of TikTok Shop users and their relationship to purchasing decisions. In addition, this study aims to determine purchasing patterns and consumer strategies in shopping activities. the method used is a quantitative approach with a questionnaire distributed through social media. The questionnaire contains four categories of questions that aim to determine purchasing patterns, shopping strategies, economic conditions and their relationship with purchasing decisions. This study reveals that the average income of Tiktokshop users belongs to the lower middle class. This condition affects consumer decisions in making purchases. On the other hand, with this income they do not feel burdened by living expenses. In addition, for some people economic conditions do not affect the pattern of their shopping activities.